Telaah Potensi Reunifikasi Tiongkok Terhadap Taiwan: Tinjauan Teori Attitudinal Factor - Kristoforus Bagas Romualdi; Saefur Rochmat (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2023)
This study attempts to examine the potential of China’s reunification of Taiwan, which has been fought for up until the time of Xi Jinping. The Chinese side has made various efforts to achieve unification, one of which is proposing the "one country, two systems" model that would make Taiwan part of a Chinese province with the high autonomy. However, Taiwan still refused the invitation to reunify China. Using an approach from integrative factor theory, specifically Michael Haas’s attitudinal factor, the researchers found that the potential for reunification will be difficult to materialize in the near future due to differences in ideology, Taiwan’s distrust of China’s involvement, Taiwan’s strengthening of identity, and US intervention. China must change its approach if it is to achieve reunification by avoiding methods of military intimidation and strongly committed to respecting the autonomy of the reunified regions to gain complete trust all of Taiwan.